Designing an Online Supervision System (Logbook) with Laravel Framework - Hadi, Ronal; Defni, -; Medrofa, Arnila Cahya (SOTVI, 2020)
Final Year Project is one of the students’ graduation requirements to get a Bachelor Degree in Higher Education. The supervising process is an essential part of the final project activity between the supervisor and the students to supervise the students to produce a qualified final project. The article aims at designing a logbook application by using the Laravel Framework for students’ supervising process. The design of the logbook used Laravel framework and a MySQL database. It is utilized by Information Technology major Politeknik Negeri Padang.